Pengantar editorial MediaPsi 9(2) 2023 - Akhrani, Lusy Asa (Mediapsi, 2023)
This introductory section summarizes the contributions in this edition of MediaPsi. This edition of Mediapsi presents articles that show people's efforts to maintain their mental health amidst the various problems they face. The first three articles present the results of research on the COVID-19 pandemic and various phenomena faced, such as resilience in COVID-19 survivors and students in the Kawruh community, as well as loneliness and suicidal ideation among students during the COVID-19 pandemic. The fourth article presents the results of research related to fathers' emotional experiences in caring for toddlers; the fifth article presents the results of research related to optimism and subjective career success in teachers; the sixth article displays the inequality phenomenon of increasing depression rates in society, which is not proportional to the increasing number of personnel and quality of professional services; and the sixth article illustrates the phenomenon of inequality in rising rates of depression in society, which deviates from increases in the number of workers and the caliber of professional services.